Deformation at the eastern margin of the Northern Canadian Cordillera: Potentially related to opening of the North Atlantic. (15th February 2019) - Enkelmann, Eva; Finzel, Emily; Arkle, Jeanette
Abstract: The Northern Canadian Cordillera (NCC) comprises the Mackenzie Mountains, which are characterized by earthquakes occurring 1, 000 km east of the western North American margin. However, no recognized convergence has occurred in this inboard region since the Mesozoic to early Cenozoic formation of the Cordillera. This lack of an obvious driver for the modern NCC deformation has generated considerable debate and various geodynamic models. We show here thermal histories derived from (U‐Th‐Sm)/He data that are interpreted to indicate reactivated deformation and formation of the eastern deformation front beginning 30 Ma. At that time the western margin of North America was mainly a transform boundary, which typically transmits very limited amount of stress into the continent. Along the northeastern margin of North America, however, the North Atlantic was opening and may have caused horizontal forces that drove deformation far to the west where the rigid craton encountered the weak Cordillera.